UK'S DESTINATION BRANDING THROUGH NETFLIX'S BRIDGERTON: SOFT POWER, SCREEN TOURISM, AND POST-PANDEMIC TOURISM RECOVERY - Pande Made Indira Pradnyani; I Made Anom Wiranata; Anak Agung Anik Kristina Dewi (Sociae Polites, 2026)
Tourism is a vital pillar of the United Kingdom's economy and national image. Following the severe disruptions caused by the COVID-19 pandemic, the UK government prioritized tourism recovery while simultaneously facing intensifying global competition and the persistent concentration of international visits in London. This study examines how the UK government strategically utilized the Netflix series Bridgerton—one of the most-watched streaming productions of all time—as a soft power instrument for destination branding to boost its post-pandemic tourism sector. Employing a descriptive qualitative method, this research applies the concepts of soft power (Nye, 1990), screen tourism (Hudson & Ritchie, 2006), and destination branding (Kartajaya, 2005; Pereira et al., 2012) as its analytical framework. The findings reveal three interconnected strategies: first, the implementation of production incentive policies through the British Cultural Test mechanism, which strengthened the authentic representation of British cultural identity, heritage, and landscapes in the series; second, the formalization of screen tourism as a national strategy through a Memorandum of Understanding between VisitBritain and the British Film Commission; and third, the integration of Bridgerton into the global 'Starring GREAT Britain' campaign (2025), which positioned the UK as an iconic filming destination, differentiated tourism offerings through Bridgerton-themed experiences, and deployed integrated promotional branding through media partnerships, B2B activities, digital platforms, and print media. These strategies contributed to the UK's post-pandemic tourism recovery, with international visitor arrivals reaching a historic record of 42.6 million in 2024, surpassing pre-pandemic levels for the first time. This case demonstrates how popular culture can function as a concrete manifestation of soft power with measurable national impacts. Keywords: Bridgerton, Destination branding, Screen tourism, Soft power, United Kingdom